2020
DOI: 10.1093/jbcr/iraa127
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Oxidation Protein Product (AOPP) Levels in Second- and Third-Degree Thermal Burns

Abstract: Burn is a systemic injury affecting the entire organism according to its etiology and severity. The aim of this study was to investigate plasma AOPP levels before and after treatment of second- and third-degree thermal burn patients and determine the changes in this parameter, and also, to find out the relationship between AOPP level and hospitalization period and total body surface area (TBSA). The study material consisted of pediatric patients with the complaint of second- and third-degree thermal burns aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Daily intake of 500 mg/kg BW of this microalgae reduced the plasma fluoride level by about 67.51%. On the other hand, the drop of plasma protein level in fluorotic animals in this study was similar to other findings 37 , 38 . In this regard, it was reported that fluoride can trigger endoplasmic reticulum stress, which in turn can reduce protein synthesis and secretion 39 .…”
Section: Discussionsupporting
confidence: 93%
“…Daily intake of 500 mg/kg BW of this microalgae reduced the plasma fluoride level by about 67.51%. On the other hand, the drop of plasma protein level in fluorotic animals in this study was similar to other findings 37 , 38 . In this regard, it was reported that fluoride can trigger endoplasmic reticulum stress, which in turn can reduce protein synthesis and secretion 39 .…”
Section: Discussionsupporting
confidence: 93%
“…Advanced oxidation protein products, an oxidative stress marker, were discovered for the first time in 1996 (31) ; proteins were vulnerable to free radical and oxidant assaults, which resulted in structural and functional changes, resulting in endothelial dysfunction. AOPPs are thought to be both indicators for prooxidant-antioxidant imbalances and mediators of inflammation since they activate mononuclear phagocytes and act as cytokine-like mediators between neutrophils and monocytes (32) . AOPP has recently been identified as a key marker for detecting the effects of oxidative stress on proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of superficial or deep involvement of the dermis, the burn injury is classified as a second-degree injury, associated with scar development in severe cases, and surgical intervention may be needed in some severe cases [ 11 ]. Third-degree burn injuries are usually painless, with involvement of the entire skin, and require surgery [ 12 ]. In the case of deep tissue damage including muscles and bones, the burn injury is fourth-degree, which usually leads to the loss of the burned limb [ 13 ].…”
Section: Introductionmentioning
confidence: 99%